Stigma management in waste management: An investigation into the interactions of 'waste pickers' on the streets of Cape Town and the consequences for agency - Peres, Teresa Sandra (Department of Sociology, 2017)
Contemporary approaches to waste management in South Africa have been driven by a desire to modernise and cleanse urban public spaces. Even though street waste pickers provide a separation-at-source service, thereby minimising waste to landfill, these people and their work continue to be stigmatised. Using Goffman's theory of stigma and impression management, this study establishes how evident stigma is in the agency of waste pickers. Agency was conceptualised using Emirbayer and Mische, to identify the management of stigma in waste pickers' choices, regarding established routines, future plans and their practical evaluation of ongoing circumstances. Following Giddens, stigma is posited as a source of both enablement and constraint to waste pickers' agential capacity. A social constructionist theoretical approach, combined with an interpretivist epistemology, was used to gather qualitative data using ethnographic methods. The first of its kind in this field, participatory fieldwork was conducted with waste pickers over the course of a year. Using a combination of thematic and discourse analysis the findings showed that stigma emerges in an insidious manner. To overcome being stigmatised by their physical appearance, waste pickers use an idealised presentation of self to position themselves as superior to criminals, illegal drug users and poor working classes. Although the capacity to overturn negative stereotypes was constrained because waste pickers were often unable to confine discrediting behaviour to back region spaces, the power of stigma was never absolute. Impression management enabled waste pickers to resist being positioned as matter out of place through their cultivation of relationships with residents and agents of social control. However, I argue that because these reciprocal relationships go largely unseen by the wider public, stigma continued to constrain the agential capacity of impression management strategies. The implication of the study is that, although agency is somewhat invisible, waste pickers are able to subvert the impact of policies designed to threaten their freedom of movement and access to waste. In achieving this, the unintended consequence is that waste pickers' agency further entrenches the stereotypical discourses that position them and their work as a threat to order in Cape Town.